Examining the Linear Cooling Characteristics of Microfluid Based on Thermoelectric Refrigeration - Wang Haoqing; Sun Dongfang; Gao Cai; Cheng Wenlong; Zhou Pei; Tang Jingchun; Zhu Junye; Han Xue; Zhang Mengfei (Zhileng xuebao, 2024)
Currently, the precise linear cooling of microfluidics remains a challenge in the development and application of microfluidic technology in medicine and life sciences. To realize the linear cooling of the target area on a microfluidic chip, a thermoelectric refrigeration-based temperature control system for microfluidic chips was designed, and linear coupling between the current, cooling capacity, and microfluidic temperature was achieved through numerical simulation and experimental tests. When the thermoelectric cooler was driven by a constant current, the linearity of the cooling process of the microfluidic sample cell was only 0.598. The use of a single-function transient current significantly improved the linearity of microfluidic cooling; however, cold surpluses and inadequacies still existed, which did not meet the accuracy requirements of linear cooling. Finally, a transient current mechanism to realize the linear cooling in microfluidic thermoelectric cooler devices was obtained by coupling a variety of current waveforms. Linear cooling of microfluidic between -19–26 °C and 24–42 °C/min was realized, and the linearity was above 0.9981. The linear cooling mechanism of the thermoelectric cooler for microfluidic devices was successfully verified by experimental tests.